The Impact of Canva-Assisted Animated Videos on Critical Thinking Skills In Elementary School Students' Mathematics Learning - Maulana, Asep; Yuliyanto, Aan; Rochim, Ahmad Abdul; Farikhin, Iing; Anam, Saepul; Herawati, Herawati (International Conference on Elementary Education, 2025)
One of the high-level thinking skills in mathematics is quite challenging for students. Critical thinking skills are one of the higher-order thinking skills that must be developed. Teachers must be able to help students learn mathematics by improving their critical thinking skills, one of which is through animated videos. This literature review, using an integrative review model, aims to examine the influence of animated videos with the help of Canva on critical thinking skills in fourth-grade elementary school students' learning of shapes material. Animated videos are innovative learning media because they systematically contain images or elements and material designed to attract the audience's attention. Animated videos can enhance and encourage students' abilities to think critically by prompting them to explain their thoughts, develop important skills, draw conclusions, give additional reasons, and come up with plans and methods. Thus, animated videos can be one of the references for improving students' thinking skills in mathematics in elementary schools.